ART EDUCATION IN PAKISTAN: COLONIAL LEGACY AND CHALLENGES OF 21st CENTURY (Proceeding of the International Conference on Arts and Humanities, 2018)
Education in the Subcontinent prior to British takeover was mostly informal.  Institutionalized formal Education in the region was introduced by the British rulers in 19th century.  Pakistan inherited the system which was divided at school, college and university levels.  The presence of art in this system is indebted to the British who opened art colleges and departments in the university later on inherited by Pakistan. The tradition of art teaching in the subcontinent was based on apprenticeship and personal coaching. This trend was duly changed in the British period and presently art education is available to every person interested in the subject.  This analytical paper focuses on the relevancy of contemporary art education with Pakistani society and the challenges faced by art institutions in the 21st century. Pre- independence and post-independence institutes of higher art education in Pakistan will be analyzed to derive conclusion.
Keywords: Art Education; Colonial legacy; apprenticeship; art teaching in Pakistan